Synthesis, Crystal Structure and Luminescent Properties of 2D Zinc Coordination Polymers Based on Bis(1,2,4-triazol-1-yl)methane and 1,3-Bis(1,2,4-triazol-1-yl)propane; Crystals; Vol. 7, iss. 12 - Semitut E. Yu. Evgeny Yurjevich; Sukhikh T. S. Taisiya Sergeevna; Filatov E. Yu. Evgeny Yurjevich; Ryadun A. A.; Potapov A. S. Andrey Sergeevich (2017, 2017)
Title screen